Expression of CD39 on Activated T Cells Impairs their Survival in Older Individuals - Fang, Fengqin; Yu, Mingcan; Cavanagh, Mary M.; Hutter Saunders, Jessica; Qi, Qian; Ye, Zhongde; Le Saux, Sabine; Sultan, William; Turgano, Emerson; Dekker, Cornelia L.; Tian, Lu; Weyand, Cornelia M.; et al. (Cell reports (Cambridge), 2016)
In an immune response, CD4+ T cells expand into effector T cells and then contract to survive as long-lived memory cells. To identify age-associated defects in memory cell formation, we profiled activated CD4+ T cells and found an increased induction of the ATPase CD39 with age. CD39+ CD4+ T cells resembled effector T cells with signs of metabolic stress and high susceptibility to undergo apoptosis. Pharmacological inhibition of ATPase activity dampened effector cell differentiation and improved survival, suggesting that CD39 activity influences T cell fate. Individuals carrying a low-expressing CD39 variant responded better to vaccination with an increase in vaccine-specific memory T cells. Increased inducibility of CD39 after activation may contribute to the impaired vaccine response with age. [Display omitted] •CD39 identifies human effector CD4 T cells that are prone to apoptosis•CD39 is more readily induced in CD4 T cell responses of older individuals•The ATPase activity of CD39 regulates effector cell differentiation and apoptosis•CD39 expression inversely correlates with T memory cell generation after vaccination Fang et al. report that the ATPase activity of CD39 regulates differentiation and apoptosis of effector T cells. They propose that increased CD39 expression in T cells with age promotes T cell apoptosis in older individuals and contributes to age-dependent impairment in responses to vaccination.